The Development and Validation of the Smell-Qx Questionnaire, Based on a Systematic Review of the Literature and the COMET Initiative on the Development of Core Outcome Sets for Clinical Trials in Olfactory Disorders - Lechner, Matt; Fjaeldstad, Alexander; Rehman, Umar; Liu, Jacklyn; Boniface, David; Boardman, Jim; Boak, Duncan; Altundag, Aytug; Frasnelli, Johannes; Gane, Simon; Holbrook, Eric; Hsieh, Julien; et al. (International forum of allergy & rhinology, 2025)
BACKGROUND: Olfactory dysfunction affects up to 22% of the population. Accurate assessment is vital for diagnosis and tracking outcomes, often using patient-reported outcome measures (PROMs). AIMS: We aimed to develop and validate a novel questionnaire for assessing olfactory and gustatory dysfunction. METHODS: A systematic review identified existing smell and taste questionnaires, followed by item generation and selection. After two Delphi cycles and consultation with a large panel of smell and taste experts, the Smell-Qx questionnaire was developed. A validation study recruited patients from smell and taste clinics (cases) and general ENT clinics (controls) to complete the Smell-Qx. Additionally, patients with smell and taste disorders underwent psychophysical testing using Sniffin' Stick Threshold, Discrimination, and Identification (TDI) tests. RESULTS: The Smell-Qx is an 11-domain instrument, with five core domains used for total score calculation and six history/quality-of-life domains for obtaining a comprehensive history. The validation study recruited 60 participants (32 patients with smell/taste disorders and 28 controls). Items showed acceptable to significant internal consistency (Cronbach's α: 0.64-0.97) and test-retest reliability (ICC: 0.65-0.99, p < 0.001). The Smell-Qx was effective at distinguishing patients with smell and taste disorders from controls (t = 9.99, df = 58, p < 0.0001). Concurrent criterion validity was good with overall SATD-related quality of life (r = 0.43, p = 0.015), as well as with the smell loss domain and overall smell TDI scores (r = -0.54, p = 0.011). CONCLUSION: The Smell-Qx is a reliable and valid PROM for assessing olfactory and self-reported gustatory disorders, capturing symptom severity and quality-of-life impact. It can integrate into a multi-modal assessment approach alongside psychophysical testing.
Keywords: patient‐reported outcome measures; olfactory dysfunction; gustatory dysfunction